2015
DOI: 10.17795/whb-23873
|View full text |Cite
|
Sign up to set email alerts
|

Explaining the Role of Health Belief Model Constructs On Physical Puberty Health Among Teen Girls: Structural Equation Modeling

Abstract: Background:The puberty as a stage of life is an important developmental process. Teen girls have numerous health care needs and their specific aspects should be considered. Objectives: In this study we applied explanatory model to determine the role of health belief model constructs on physical puberty health among teen girls. Materials and Methods:This correlational cross-sectional study was conducted in 2011, and attempted to determine the total, indirect and direct effects of health belief model construct o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 19 publications
3
6
0
Order By: Relevance
“…Increased understanding of the benefits of having healthy behaviors and reducing the barriers of engaging in these behaviors also significantly stimulates healthy behaviors, including preventive behaviors against CL [7,15,28]. Therefore, it is recommended that specific educational approaches, such as group discussion and role-playing are used when implementing educational interventions to promote preventive behaviors against CL [26,27].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Increased understanding of the benefits of having healthy behaviors and reducing the barriers of engaging in these behaviors also significantly stimulates healthy behaviors, including preventive behaviors against CL [7,15,28]. Therefore, it is recommended that specific educational approaches, such as group discussion and role-playing are used when implementing educational interventions to promote preventive behaviors against CL [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the cues to action construct had a direct, positive, and statistically significant effect on the preventive behavior against CL. Based on the results of other studies, the cues to action has been a significant predictor of adopting healthy behaviors, including preventive behaviors against CL [15,28]. It has also been suggested that educational interventions are effective in improving the cues to health action [7], and cues to action is a predictor of healthy behaviors [15,28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The data collection tool was one questionnaire by Kazemi et al and Shirzadi et al [ 15 , 16 ]. To obtain the questionnaire validity, the tool was examined by seven faculty members and research experts (three health specialists, two obstetricians, and two statisticians and epidemiologists).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, theory-based research in diverse populations and cultures opens new avenues for social psychologists interested in youth development, health, and education [ 13 ]. Based on the results of one study on girls' puberty health in Tehran, perceived benefits and barriers were the most important predictive constructs [ 14 ] The results of two intervention studies based on HBM in adolescent female students indicated the effectiveness of HBM-based education in adopting puberty behaviors, thereby promoting maturity and improving the physical performance and perception of the individuals [ 15 , 16 ]. It should be noted that a similar study has not been conducted in Guilan province.…”
Section: Introductionmentioning
confidence: 99%